Transcatheter Mitral Valve Replacement After Surgical Repair or Replacement: Comprehensive Midterm Evaluation of Valve-in-Valve and Valve-in-Ring Implantation From the VIVID Registry. Issue 2 (12th January 2021) - Simonato, Matheus; Whisenant, Brian; Ribeiro, Henrique Barbosa; Webb, John G.; Kornowski, Ran; Guerrero, Mayra; Wijeysundera, Harindra; Søndergaard, Lars; De Backer, Ole; Villablanca, Pedro; Rihal, Charanjit; Eleid, Mackram; et al.
Abstract : Background: Mitral valve-in-valve (ViV) and valve-in-ring (ViR) are alternatives to surgical reoperation in patients with recurrent mitral valve failure after previous surgical valve repair or replacement. Our aim was to perform a large-scale analysis examining midterm outcomes after mitral ViV and ViR. Methods: Patients undergoing mitral ViV and ViR were enrolled in the Valve-in-Valve International Data Registry. Cases were performed between March 2006 and March 2020. Clinical endpoints are reported according to the Mitral Valve Academic Research Consortium (MVARC) definitions. Significant residual mitral stenosis (MS) was defined as mean gradient ≥10 mm Hg and significant residual mitral regurgitation (MR) as ≥ moderate. Results: A total of 1079 patients (857 ViV, 222 ViR; mean age 73.5±12.5 years; 40.8% male) from 90 centers were included. Median STS-PROM score 8.6%; median clinical follow-up 492 days (interquartile range, 76–996); median echocardiographic follow-up for patients that survived 1 year was 772.5 days (interquartile range, 510–1211.75). Four-year Kaplan-Meier survival rate was 62.5% in ViV versus 49.5% for ViR ( P <0.001). Mean gradient across the mitral valve postprocedure was 5.7±2.8 mm Hg (≥5 mm Hg; 61.4% of patients). Significant residual MS occurred in 8.2% of the ViV and 12.0% of the ViR patients ( P =0.09). Significant residual MR was more common in ViR patients (16.6% versus 3.1%; P <0.001) and was associated with lower survival at 4 years (35.1% versus 61.6%; P =0.02). The rates of Mitral Valve Academic Research Consortium–defined device success were low for both procedures (39.4% total; 32.0% ViR versus 41.3% ViV; P =0.01), mostly related to having postprocedural mean gradient ≥5 mm Hg. Correlates for residual MS were smaller true internal diameter, younger age, and larger body mass index. The only correlate for residual MR was ViR. Significant residual MS (subhazard ratio, 4.67; 95% CI, 1.74–12.56; P =0.002) and significant residual MR (subhazard ratio, 7.88; 95% CI, 2.88–21.53; P <0.001) were both independently associated with repeat mitral valve replacement. Conclusions: Significant residual MS and/or MR were not infrequent after mitral ViV and ViR procedures and were both associated with a need for repeat valve replacement. Strategies to improve postprocedural hemodynamics in mitral ViV and ViR should be further explored. Abstract : Supplemental Digital Content is available in the text.